Students’ Motivation In Learning English By Using Blended Learning SMK HKBP Pematangsiantar - Rina Octavia Simarmata; Febrika Dwi Lestari (Departement of Mathematics Education, 2023)
This research aims to determine the components of student motivation in learning English with blended learning in class XI students at SMK HKBP Pematangsiantar. Therefore, the formulation of the problem in this study is